The Transformation of the Tour Guide's Role into a Cultural Interpreter in Bali - Ida Bagus Putu Puja; Ni Putu Evi Wijayanti; Putu Ayu Aryasih; Putu Gde Arie Yudhistira; I Gede Ngurah Primanda S Rahadiarta (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study examines the transformation of the tour guide’s role into that of a cultural interpreter in Bali, investigating how cultural interpretation quality influences tourists’ understanding of local cultural values and the formation of meaningful tourism experiences. The primary novelty lies in simultaneously integrating Heritage Interpretation Theory and Intercultural Communication Theory within a single empirical framework and in explicitly connecting micro-level interpretive practices with macro-level policy and competency standards (SKKNI) a linkage absent from prior research. An explanatory sequential mixed-methods design was employed, comprising a quantitative survey of 247 tourists (domestic and international) across four major Balinese cultural destinations, followed by qualitative in-depth interviews with 12 certified tour guides and 8 tourism policymakers. The findings revealed that cultural interpretation quality and tourists’ cultural value understanding were significant positive predictors of meaningful tourism experiences, together explaining 47% of outcome variance. Qualitative findings revealed a structural gap between evolving interpretive field practices and SKKNI standards that remain technically oriented. This study advances cultural tourism theory by positioning the tour guide as a pedagogical actor whose interpretive role requires systemic institutionalisation through policy reform and competency reorientation toward reflective, value-based guiding.